Czech Republic : 2016 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Czech Republic. (IMF Staff Country Reports; Country Report ;, 2016)
A favorable external environment, high utilization of EU funds, and supportive macroeconomic policies have boosted economic growth. The authorities' medium-term fiscal objective is appropriate, but fiscal framework legislation that would anchor policy is yet to be approved by parliament. The central bank's use of an exchange rate floor to achieve its inflation target has helped stem deflationary pressures, but inflation is still well below target. The financial system is sound and resilient to shocks. Policy recommendations. Policies should aim at comprehensively addressing obstacles to strong and sustained growth, while safeguarding macroeconomic stability.